Improvement of Overall Equipment Effectiveness (OEE) through Implementation of Autonomous Maintenance in Crankcase Line - A. R., Razali; M., Ishak; Mohd Azam, Musa; Nazrul Idzham, Kasim; Wan Ahmad Najmuddin, Wan Saidin (Trans Tech Publications, Switzerland, 2015)
A study on Autonomous Maintenance (AM) implementation was conducted for CNC machine at automotive components manufacturing line in order to identify and measure equipment losses related to availability, performance and quality rate. These values were used to determine the overall equipment effectiveness (OEE) of the manufacturing line before and after AM implementation. The project started with AM team formation before it was continued with 5S activities and fuguai (abnormality) detection and restoration. Kaizen was used for continuous improvement to restore deteriorated parts and components of the machine. Autonomous Maintenance standards such as cleaning, lubricating and inspection were developed. The AM team members consistently followed the operator maintenance standards to ensure that machine is always in good working condition. The OEE results were taken daily after AM implementation and compared with the data before the implementation. The average OEE result shows significant improvement from 65.8% to 80.4% after the AM implementation. However, the result still did not achieve the company’s target. The main reason was because the machine was very old, which almost reaches deterioration stage according to the bath tub curve. Some recommendations are suggested as to push the OEE value closer to the company’s target including a review on other pillars in Total Productive Maintenance (TPM).